The determinants of festival participants' event loyalty: a focus on millennial participants - Ho, Jie Min; Tiew, Fidella; Adamu, Adamu Abbas (2022)
Purpose: This study aims to determine how different event quality dimensions (i.e. information availability, program content, food, staff service, merchandises, ticketing, facility and convenience) individually affect the satisfaction of millennial festival participants, and how their satisfaction subsequently influence their behavioral intention. Design/methodology/approach: The research hypotheses were tested with a sample of 272 millennial participants attending the Borneo Jazz Festival held in Miri, Sarawak. Findings: The results indicated that program content and facility are crucial predictors of millennial participants' level of satisfaction with the event. Furthermore, the level of satisfaction would, in turn, affect their intention to revisit the event and spread positive word-of-mouth. Research limitations/implications: The results are expected to assist festival planners in managing and designing festivals that can appeal to millennials who make up a significant percentage of tourism market. Originality/value: The study adds to the knowledge of how music festival environment can yield loyalty amongst millennial festival participants in Sarawak, an Eastern state of Malaysia on the island of Borneo.